Forma Escolar E Cuidado No Retorno Do Aluno Na Escola Após O Tratamento Oncológico: Investigando A Literatura Sobre O Tema - Vilar, Ligia Perez [UNIFESP] (2017)
The following study is set at the border between Education and Health, in other words, a field that is still under construction. With a movement searching for the directions to Scholar manner and Care, we aimed to answer the research problem: How are conceptually understood the terms scholar manner and cares in the scientific articles when these make reference to the student return to the primary school after an oncological treatment? We based the problem specifications and its delimitations in four scientific literature lines: (1) Scholar manner; (2) Scholar abilities and skills; (3) Clinical educational service in the national education; (4) Clinical Class in the educational inclusive area. We adopted predominantly the qualitative methodological approach in the exploratory aspect of knowledge construction. Besides, this study constructs the information based in the documental analyses of the content. The literature from the lines mentioned guided us in the articles systematization and their different phases: documental survey, pre-analysis, material exploration, information construction and results treatment. In conclusion, we were served with distinct conception- Scholar manner and Care- to understand the return to the student regular school after they had done the oncological treatment and we achieved two hypotheses constructions as the exploratory research demands. In the first hypotheses we argued about the education space of the severely ill student- In the research time the Education and Health field assumed a learner counter, this way, in the circularity way at the same time that he learns by the results of complex structures integration, he produces his own research objects. If in the first hypothesis the focus was the space, the second was the usage of a state of complementary Manner- Scholar-Care, can by hypotheses , be affirmed by research when they get directed to the active investigation directed to the problem resolution. Utopically we understand that the rationalization in both stages of knowledge established by the listed hypothesis, helped to a satisfactory return to the severely ill student original school.